Botulinum Neurotoxin Application to the Severed Femoral Nerve Modulates Spinal Synaptic Responses to Axotomy and Enhances Motor Recovery in Rats - Marcel Irintchev; Orlando Guntinas-Lichius; Andrey Irintchev (Neural Plasticity)
Botulinum neurotoxin A (BoNT) and brain-derived neurotrophic factor (BDNF) are known for their ability to influence synaptic inputs to neurons. Here, we tested if these drugs can modulate the deafferentation of motoneurons following nerve section/suture and, as a consequence, modify the outcome of peripheral nerve regeneration. We applied drug solutions to the proximal stump of the freshly cut femoral nerve of adult rats to achieve drug uptake and transport to the neuronal perikarya. The most marked effect of this application was a significant reduction of the axotomy-induced loss of perisomatic cholinergic terminals by BoNT at one week and two months post injury. The attenuation of the synaptic deficit was associated with enhanced motor recovery of the rats 2–20 weeks after injury. Although BDNF also reduced cholinergic terminal loss at 1 week, it had no effect on this parameter at two months and no effect on functional recovery. These findings strengthen the idea that persistent partial deafferentation of axotomized motoneurons may have a significant negative impact on functional outcome after nerve injury. Intraneural application of drugs may be a promising way to modify deafferentation and, thus, elucidate relationships between synaptic plasticity and restoration of function.